(untitled) (Advancements in Homeopathic Research, 2022)
Urticaria is a type of local dermal inflammation of skin disease. Urticaria is a multifatorial cause such as insect bites or food, food additives, insect bites, psychogenic, physical factors or some drugs. Homoeopathy has an effective treatment for a skin disease which includes urticaria. Selection of the medicine based on the individual symptoms of the patient. Cases summary: This is a case of a patient was suffering from chronic facial urticaria having redness, itching, and swelling of face. The patients were prescribed indicated constitutional Homoeopathic medicines. Individualised homoeopathic medicine Rhus toxicodendron was prescribed in centesimal potency which showed a positive role in the treatment of chronic facial urticaria. Within five months urticaria on face was annihilated. There was no recurrence over the next near about 2 years.